Mini-Computer-based Appointment Scheduling for Ambulatory Patients) - Ratzer, G.; Fletoher, Suzanne W.; Pollack, M.; Fletcher, H. (Methods of Information in Medicine, 1978)
A fast, reliable and flexible appointment system is essential for ambulatory medical care facilities attempting to provide high quality medical care; computerization has helped meet these objectives. To date, however, central computing facilities have been used. These have been too expensive for widespread use, and their programs have not included specific features necessary to improve the quality of patient care. To overcome these limitations, a system was designed which can be implemented on a mini-computer, and which incorporates a variety of capabilities promoting personalized medical care in a busy clinic environment. This on-line system potentially can handle up to 250,000 patient visits/ year.Three files store the necessary data base: a patient file, an appointment file, and a physican file. Simple commands and special access techniques are used. In addition to on-line appointment making, confirming and cancelling functions, the system can communicate with patients of several languages; send reminder postcards; promote continuity of care by keeping track of which patients belong to each physician; enable each physician to determine his own clinic schedule routine; and provide physicians with master lists of their patients, including address, telephone number, and summaries of important medical information.The development of automated appointment systems on mini-computers permits widespread implementation in ambulatory medical care.
Keywords: Automated Patient Scheduling; Mini-Computer; Appointment-Making